-5(6m+5)=-25-3m

Simple and best practice solution for -5(6m+5)=-25-3m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(6m+5)=-25-3m equation:


Simplifying
-5(6m + 5) = -25 + -3m

Reorder the terms:
-5(5 + 6m) = -25 + -3m
(5 * -5 + 6m * -5) = -25 + -3m
(-25 + -30m) = -25 + -3m

Add '25' to each side of the equation.
-25 + 25 + -30m = -25 + 25 + -3m

Combine like terms: -25 + 25 = 0
0 + -30m = -25 + 25 + -3m
-30m = -25 + 25 + -3m

Combine like terms: -25 + 25 = 0
-30m = 0 + -3m
-30m = -3m

Solving
-30m = -3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '3m' to each side of the equation.
-30m + 3m = -3m + 3m

Combine like terms: -30m + 3m = -27m
-27m = -3m + 3m

Combine like terms: -3m + 3m = 0
-27m = 0

Divide each side by '-27'.
m = 0

Simplifying
m = 0

See similar equations:

| 8x+11+3x=13-7x+4 | | 4h-I+3h-5i+h= | | -12(x+3)+4(4x-3)=3(x-6)+14 | | 16=4w+9 | | -11+5n=-91 | | 5(-7b-7)= | | X-10=2x+4 | | d-14.25=23.5 | | 8+3b=-1+3(3+b) | | 3/4-1+1/2x=3/8x+1/4 | | 2x-3+x=3x+1 | | -3(x-1)=2x+48 | | 5(x-7)+x=6(x-7)+7 | | x^2-16x=.35 | | 5(x-1)2x=2x-5 | | -7y+26=-3(y-6) | | X+11+x+14=17 | | 6n-3n+3120=5400 | | 8(-5b+7)+4b= | | 1250=50+30x | | p-49=5(p+3) | | -30-5n=-6(n+4) | | -135/-9=15 | | 10(s-6)=-149 | | 8x+11+3=23-7x+4 | | 5(v-3)=-9v-29 | | 44c+49=457c-7 | | 8(X-1)=-2x+52 | | 9(x+1.4)=18 | | -3(6x-8)+7=-18+31 | | 2(x+7)+6=2x+2 | | 7x=5(2x-5) |

Equations solver categories